(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: Colostomy was used for treatment of colorectal injuries since the 2nd World War, and it is a lifesaving procedure. There is a trend towards primary closure of colorectal injuries without colostomy in hemodynamically stable patients. Objective: To evaluate the safety of primary closure of colorectal injuries without colostomy in hemodynamically stable patients. Methods: A cross sectional study was performed at Al-Imamein Al-Kadhimein Medical City for patients with colorectal injuries over the period from July 2011 to July 2017. Management was started with active resuscitation of the patient, explorative laparotomy (securing hemorrhage) and assessment of the colorectal injuries. When the patients were stable hemodynamically without associated injuries to other parts of the body; debridement of the wound edges of the colon and primary repair by suturing in two layers using 2/0 absorbable suture (polyglactin) on a round needle with or without colostomy. But if the patients were in a shock state with multiple associated injuries to other parts of the body, with severely devascularized lacerated colon; proximal colostomy was done as a part of damage control surgery with resection of the devascularized segment and suturing of the distal end of the colon. Results: A total of 231 patients sustained colorectal injuries; 143 (61.90%) males and 88 (38.09%) females. The age of the patients ranged from 6-76 years, mean age was 32.16±76 year. Colostomy was done for 134 (58.01%) patients. Primary repair without colostomy were done for 97 (41.99%) patients. Postoperative follow up of the patients treated with primary repair of colorectal injuries without colostomy were detected collection and leaking repaired segment of colon in 5 (5.15%) patients. Re-exploration of the abdomen and colostomy were done for them. There was no mortality in patients treated without colostomy. The mortality rate was 9 (6.71%) for patients treated by colostomy due to associated multiple traumas to other parts of the body. Conclusion: Primary repair of colorectal injuries without colostomy are safe in a hemodynamically stable patient without associated injuries to other parts of the body. Keywords: Colorectal injury, primary repair, colostomy. Citation: Atiyah TS. Safe primary repair of colorectal injuries without diverting colostomy. Iraqi JMS. 2018; 16(3): 258-267. doi: 10.22578/IJMS.16.3.5